The effect of spin level and ball exit speed on forearm muscle activity in the tennis forehand stroke - Rigozzi, C.; Cox, J.; Vio, G. A.; Martens, W. L.; Poronnik, P. (International Journal of Sports Science & Coaching, 2022)
Elbow tendinopathy injuries are very common in tennis players. One of the commonly accepted theories describing the development of elbow tendinopathy in tennis is based on stiffness of the forearm skeletal muscle units and their repetitive overuse in the forehand stroke. Our objective was to use a novel microcontroller based wearable device to compare the influence of different forehand spin levels (flat, topspin and lob) and ball exit speed on forearm muscle activity in the potential onset of elbow tendinopathy in experienced adult tennis players. Peak normalised extensor carpi radialis (ECR) and flexor carpi radialis (FCR) muscle activity corresponding to each forehand shot and ball exit speed were determined and analysed. For the ECR shots (flat = 121, topspin = 272 and lob = 273) by 8 players, Kruskal-Wallis test (p < 0.001) and Post-Hoc tests revealed a significant difference between the flat and topspin spin levels (p < 0.01) and flat and lob spin levels (p < 0.001). For the FCR shots (flat = 125, topspin = 301 and lob = 303) by 9 players, Kruskal-Wallis test showed no significant difference between the three spin levels. For the corresponding ball speed, the Kruskal-Wallis (p < 0.001) and subsequent Post-Hoc (p < 0.001) showed that flat hits had the significantly highest ball speed followed by topspin then lob accordingly for both muscles included shots. Our results suggest that coaches could consider recommending players to hit forehands with topspin in order to potentially reduce the risk of developing lateral elbow tendinopathy.